2014
DOI: 10.1016/j.rehab.2014.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Effort training in Parkinson's disease: A systematic review

Abstract: There is evidence that aerobic and strength training improve physical habilities of patients suffering from Parkinson's Disease. Rehabilitation programs should be discussed with the patient, taking in account his difficulties and his physical capacities. Two questions are debatable: exercise intensity and phase ON / phase OFF timing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 73 publications
2
24
0
6
Order By: Relevance
“…33 In the present study, almost half of the patients reported chewing and swallowing problems in the NOT-S. non-pharmacological aids in PD. 35,36 Our results showed that it was possible to reduce the impact of the disease on the oral function and hygiene both evaluated after 2 and 4 months. 35,36 Our results showed that it was possible to reduce the impact of the disease on the oral function and hygiene both evaluated after 2 and 4 months.…”
Section: Discussion and Con Clus I Onmentioning
confidence: 70%
See 1 more Smart Citation
“…33 In the present study, almost half of the patients reported chewing and swallowing problems in the NOT-S. non-pharmacological aids in PD. 35,36 Our results showed that it was possible to reduce the impact of the disease on the oral function and hygiene both evaluated after 2 and 4 months. 35,36 Our results showed that it was possible to reduce the impact of the disease on the oral function and hygiene both evaluated after 2 and 4 months.…”
Section: Discussion and Con Clus I Onmentioning
confidence: 70%
“…2,34 Thus, general stretching and flexibility exercises and rhythmic body activity improve and preserve both range of movement of the joints and gait capacity. 35,36 Our results showed that it was possible to reduce the impact of the disease on the oral function and hygiene both evaluated after 2 and 4 months. This has not been shown before.…”
Section: Discussion and Con Clus I Onmentioning
confidence: 70%
“…Although studies point to the benefits of physical therapy treatment in improving motor dysfunctions in PD (Lima, Scianni, & Rodrigues-de-Paula, 2013;Paillard, Rolland, & de Souto Barreto, 2015;Shu et al, 2014;Tambosco, Percebois-Macadré, Rapin, Nicomette-Bardel, & Boyer, 2014), few are those with an emphasis on muscle and pulmonary dysfunctions and verify the benefits of inspiratory muscle training (IMT) in this population. Inzelberg et al (2005) observed improvement in inspiratory muscle strength and endurance and improvement in the perception of dyspnoea in individuals with PD after IMT.…”
mentioning
confidence: 99%
“…Houve melhora no processo de reabilitação da DP nos últimos anos, especialmente da terapia motora e da fala (Tambosco et al, 2014). Petzinger et al, 2010 mostraram que o exercício promove melhora na neurotransmissão dopaminérgica e glutaérgica por meio de processos ativo-dependentes e modula a hiperexcitabilidade cortical dos Gânglios da Base.…”
Section: Tratamento Fisioterápicounclassified
“…Os objetivos dos programas de cinesioterapia para pacientes com DP dependem do estágio da doença (Tassorelli et al, 2009 (Tambosco et al, 2014).…”
Section: Tratamento Fisioterápicounclassified